Komunikasi Politik Salam Gotong Royong dalam Pemilihan Legislatif Kota Denpasar Tahun 2019 (Jurnal Nawala Politika, 2023)
This study aims to find out how the political communication strategy of greeting mutual cooperation became a winning instrument for I Nyoman Gede Sumara Putra in the 2019 Denpasar City legislative election. The theory of political communication by Harold D. Lasswell was used as an analytical knife using qualitative methods through interviews, the results obtained research as follows: I Nyoman Gede Sumara Putra conveys a political message based on mutual cooperation stalls that can help the economy of residents in each banjar with a direct approach to the people of North Denpasar with the help of a mutual cooperation team and mande volunteers as well as through social media and print media so that they are elected as members the Denpasar City legislature for the 2019-2024 period with the acquisition of 4,145 votes, with the most votes obtained in Ubung Kaja Village with 2,455 votes.